"Am I doing it wrong?" critically examining mediation in lesson rehearsal. (July 2020) - Peercy, Megan Madigan; Troyan, Francis John
Abstract: Drawing upon activity theory, specifically the rules for participation and the division of labor, we make a case for opening up the pedagogies of rehearsal to a broader range of collaborative interactions. By identifying a lack of theoretical clarity in the existing literature on rehearsal and providing an example of a more collective and multivoiced approach, we aim to advance theoretical considerations guiding practice-based pedagogies of teacher education. Highlights: We explore teacher educator and teacher learner interactions in rehearsal. We raise questions about purposes and approaches in the pedagogies of rehearsal. We aim to align practice-based teacher education with its sociocultural intentions. We use activity theory to broaden the possibilities in the pedagogies of rehearsal. Everyone in the rehearsal space has the potential to mediate learning.